14 Individual treatment selection for acute achilles tendon rupture based on the copenhagen achilles length measurements (CALM). (April 2019) - Barfod, Kristoffer Weisskirchner; Swennergren Hansen, Maria; Sandholdt, Håkon; Boesen, Anders; Holmich, Per; Troelsen, Anders; Tange Kristensen, Morten
Abstract : Background: Acute Achilles tendon rupture (ATR) can be treated operatively or non-operatively. An evidence based selection tool is needed to guide choice of treatment. Purpose: To investigate if treatment selection in patients with ATR can be guided by Amlang's ultrasound classification (AmC) or the Copenhagen Achilles Length Measurement (CALM). Methods: The study was performed as a prospective cohort study. Patient were 18 to 70 years and treated non-operatively. AmC and CALM were performed at baseline and correlated to outcome at 1 year. The primary outcome was the Achilles tendon Total Rupture Score (ATRS). Secondary outcomes were: heel-rise-work test, re-rupture rate and CALM at 1 year. ROC analysis was performed to determine a cut off for acceptable elongation of CALM at baseline given that elongation at 1 year was not to exceed 10%. ClinicalTrial.gov Identifier: NCT02062567 . Results: CALM was performed at baseline in 130 patients and AmC in 109. AmC showed no statistically significant correlation to any outcome parameter. CALM at baseline correlated to CALM at 1 year r=0.214 (p<0.01). The ROC model had AUC=0.67. An elongation of 7% at baseline had a sensitivity of 0.77 and specificity of 0.50. Conclusions: Elongation of the Achilles tendon at baseline measured with CALM was weakly correlated to elongation at 1 year follow up suggesting that CALM at base line can predict elongation at one year. A cut off of 7% elongation at baseline would have caught 77% of patients who ended up with an elongation above 10% at 1 year.